2018
DOI: 10.1155/2018/9712647
|View full text |Cite
|
Sign up to set email alerts
|

Development and Utilization of 3D Printed Material for Thoracotomy Simulation

Abstract: Medical simulation is a widely used training modality that is particularly useful for procedures that are technically difficult or rare. The use of simulations for educational purposes has increased dramatically over the years, with most emergency medicine (EM) programs primarily using mannequin-based simulations to teach medical students and residents. As an alternative to using mannequin, we built a 3D printed models for practicing invasive procedures. Repeated simulations may help further increase comfort l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Overall, 8 of the 31 studies specifically discussed that their 3DP models were either cheaper or of similar price to conventional models [16,17,31,34,35,37,38,41]. This decrease in price can reach up to 250% which provides a strong motive for furthering the implementation of 3DP technology in critical care [17].…”
Section: Results Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 8 of the 31 studies specifically discussed that their 3DP models were either cheaper or of similar price to conventional models [16,17,31,34,35,37,38,41]. This decrease in price can reach up to 250% which provides a strong motive for furthering the implementation of 3DP technology in critical care [17].…”
Section: Results Interpretationmentioning
confidence: 99%
“…The feedback was used and they were able to modify the gelatin used to make it more stable and increase the compressibility of the venous system. No Yates E. et al [ 35 ] Thoracotomy Technical report and quasi experiment Created a thoracotomy model and tested it on EM residents using before and after questionnaires EM residents 21 The questionnaires showed that the 3DP model increased their confidence of performing the procedure. Yes Bettega A.L.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, while two previous studies have created curriculum to teach EDT, neither has assessed for competence or mastery learning. 12 , 13 Both have been small pilot studies showing improvement in confidence performing the procedure after a curriculum intervention but not mastery of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 , 7 High- fidelity simulation models are increasingly being employed to allow for repetitive practice; however, no competency-based curriculum currently exists for EDT. 10 – 13 …”
Section: Introductionmentioning
confidence: 99%
“…In general, commercial medical training models are no option for CO 2 studies, because they are not designed to be gastight and are expensive. Thus, we took inspiration from some low-cost and "home-made" alternatives that have been developed, especially for student training in emergency thoracotomy [10][11][12]. We dedicated this technical report to give a detailed description of a thoracotomy model that is specifically designed for CO 2 field-flooding studies and can also be used for training other surgical procedures.…”
Section: Introductionmentioning
confidence: 99%